Changes in soil microbial diversity and control of Fusarium oxysporum in continuous cropping cucumber greenhouses following biofumigation - Meng, Lingbo; Runzhi Zhang, Chunyi Zhang, Xiaotong Yao, Zichao Yang; S. Li, T. Liu, C. Zheng, X. Wang, N. Xu (Emirates Journal of Food and Agriculture, 2018)
Soil biofumigation with Brassia plant parts has been demonstrated to suppress soil-borne pathogens. This effect has been attributed to the bactericidal effect of their glucosinolate degradation products. However, little is known regarding the effect of biofumigation on the microbial community structure and control of Fusarium oxysporum in continuous cropping cucumber systems. Field and pot experiments were performed to study the effect of biofumigation with brassica crops of different glucosinolate contents on the microbial diversity and control of Fusarium oxysporum during the cucumber growth period in a continuous cropping culture system. Samples collected from biofumigation and control treatments differed in the number of soil bacterial bands observed by denaturing gradient gel electrophoresis (DGGE) profiling, suggesting that biofumigation changed the soil microbial diversity. Compared with control and chemically-fumigated (HY) soils, the biofumigated soil exhibited significantly higher Shannon-Weaver diversity indices for bacteria and fungi. Cluster analysis and principal component analysis revealed that soil bacteria communities were different in the hymexazol (HY)-treated soils compared with the communities before biofumigation (BB) and those in the no fumigation (CK) groups. This was true for the mustard containing high glucosinolates (MHG), mustard containing low glucosinates (MLG), mustard (MU), and turnip (TU) groups. Pot experiments demonstrated that the amounts of Fusarium oxysporum in MHG- and HY-treated soils were significantly lower than those in other biofumigation treatments. These results demonstrate the potential utility of Brassica crops in the control of Fusarium wilt in continuous cucumber cropping systems, and the control effect of MGH was the best compared with other treatments, which could effectively reduce Fusarium oxysporum in soil by more than 60%.